Pollution slightly enhances atmospheric cooling by low-level clouds in tropical West Africa - V. Hahn; V. Hahn; R. Meerkötter; C. Voigt; C. Voigt; S. Gisinger; D. Sauer; V. Catoire; V. Dreiling; H. Coe; C. Flamant; S. Kaufmann; et al. (Atmospheric Chemistry and Physics, 2023)
Reflection of solar radiation by tropical low-level clouds has an important cooling effect on climate and leads to decreases in surface temperatures. Still, the effect of pollution on ubiquitous tropical continental low-level clouds and the investigation of the related impact on atmospheric cooling rates are poorly constrained by in situ observations and modeling, in particular during the West African summer monsoon season. Here, we present comprehensive in situ measurements of microphysical properties of low-level clouds over tropical West Africa, measured with the Deutsches Zentrum für Luft- und Raumfahrt (DLR) aircraft Falcon 20 during the DACCIWA (Dynamics–Aerosol–Chemistry–Cloud Interactions in West Africa) campaign in June and July 2016. Clouds below 1800 m altitude, identified as boundary layer clouds, were classified according to their carbon monoxide (CO) pollution level into pristine and less polluted clouds (CO < 135 ppbv) and polluted low-level clouds (CO > 155 ppbv) as confirmed by the linear CO to accumulation aerosol number concentration correlation. Whereas slightly enhanced aerosol background levels from biomass burning were measured across the entire area, clouds with substantially enhanced aerosol levels were measured in the outflow of major coastal cities, as well as over rural conurbations in the hinterlands. Here we investigate the impact of pollution on cloud droplet number concentration and size during the West African monsoon season. Our results show that the cloud droplet number concentration (CDNC) measured in the size range from 3 to 50 µm around noon increases by 26 % in the elevated aerosol outflow of coastal cities and conurbations with elevated aerosol loadings from median CDNC of 240 cm−3 (52 to 501 cm−3 interquartile range) to 324 cm−3 (60 to 740 cm−3 interquartile range). Higher CDNC resulted in a 17 % decrease in effective cloud droplet diameter from a median deff of 14.8 µm to a deff of 12.4 µm in polluted clouds.